2018
DOI: 10.2147/copd.s161410
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of a health coaching self-management program in patients with COPD: a qualitative content analysis

Abstract: PurposeTo describe the experiences of patients with COPD participating in a health coaching self-management program.Patients and methodsTwenty patients who had participated in a 6-month health coaching self-management program intervention were purposefully selected for a qualitative evaluation of the program using semi-structured interviews. The interviews were analyzed using inductive qualitative content analysis.ResultsFour categories and 13 subcategories emerged describing the participants’ experiences of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The financing level and reimbursement ratio for free medical insurance are higher than those for other types of medical insurance (Du & Lv, 2017). A Chinese survey indicated that patients with COPD who enjoy free medical insurance have better health literacy (L. Wang, 2012). This may be because patients who enjoy free medical care generally have better occupational backgrounds and social status, less financial pressure, and more chances to acquire health knowledge (L. Wang, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The financing level and reimbursement ratio for free medical insurance are higher than those for other types of medical insurance (Du & Lv, 2017). A Chinese survey indicated that patients with COPD who enjoy free medical insurance have better health literacy (L. Wang, 2012). This may be because patients who enjoy free medical care generally have better occupational backgrounds and social status, less financial pressure, and more chances to acquire health knowledge (L. Wang, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Even when patients with COPD are physically able, they have difficulty performing activities of daily living due to their low self-efficacy. Wang et al reported that a continuous self-care program could improve lung performance and physical activity and enhance the quality of life of COPD patients (Wang et al 2018). In particular, people with COPD may develop a low expectation of their self-efficacy to manage their breathing difficulties when performing certain activities.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this program improved the QoL of these patients [22]. Moreover, Wang et al reported that a continuous self-care program could improve the pulmonary performance and physical activity in COPD patients and increase their QoL [23].…”
Section: Discussionmentioning
confidence: 99%